1993
DOI: 10.1002/cne.903360105
|View full text |Cite
|
Sign up to set email alerts
|

Monosynaptic innervation of trigeminal motor neurones involved in mastication by neurones of the parvicellular reticular formation

Abstract: In order to determine whether neurones in the parvicellular reticular formation are in direct synaptic contact with motor neurones innervating masticatory muscles, a combined retrograde and anterograde transport study was carried out in the rat at both light and electron microscopic levels. The animals received injections of the retrograde tracers wheat germ agglutinin conjugated to horseradish peroxidase or cholera toxin B conjugated to horseradish peroxidase into the masticatory muscles and of the anterograd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
27
0
3

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 58 publications
3
27
0
3
Order By: Relevance
“…Mizuno et al (1978Mizuno et al ( , 1983 characterized boutons in Vmo that relay information from the region dorsal to the contralateral trigeminal motor nucleus. Other boutons within Vmo can be anterogradely labeled from the parvicellular reticular formation and have been shown to synapse with retrogradely labeled trigeminal motoneurons (Mogoseanu et al, 1993). Using intracellular horseradish peroxidase (HRP) labeling, described neurons that could be electrically stimulated from the masseter nerve, some of which synapse within the trigeminal motor nucleus.…”
mentioning
confidence: 99%
“…Mizuno et al (1978Mizuno et al ( , 1983 characterized boutons in Vmo that relay information from the region dorsal to the contralateral trigeminal motor nucleus. Other boutons within Vmo can be anterogradely labeled from the parvicellular reticular formation and have been shown to synapse with retrogradely labeled trigeminal motoneurons (Mogoseanu et al, 1993). Using intracellular horseradish peroxidase (HRP) labeling, described neurons that could be electrically stimulated from the masseter nerve, some of which synapse within the trigeminal motor nucleus.…”
mentioning
confidence: 99%
“…We chose the alligator, the human being and the rat as large, medium and small jaw samples. The position of the MTN innervating masticatory muscles is considered to be practically the same in various animals such as rats (Card et al, 1986;Limwongse & DeSantis, 1977;Mogoseanu et al, 1993;Weijs et al, 1993), cats (Mizuno et al, 1975), guinea pigs (Hecht et al, 1993;Uemura et al, 1982), rabbits (Matsuda et al, 1978) and macaque monkeys (Mizuno et al, 1981), although there might be slight differences in the MTN depending on the animal considered. No data, however, have been included in the literature concerning the morphometric analysis of neurons in the MTN from a comparative point of view.…”
mentioning
confidence: 99%
“…As for the neuropil indices, the value was in descending order: alligator, human being and rat; whereas for the circularity ratio of neuronal cell bodies, the order was: rat, alligator, and human being. We concluded that the size of motor neurons in the MTN may be related to the power of masticatory muscles, and there may be a connection between jaw sizes and shapes and sizes of the motor neurons in the MTN.The motor trigeminal nucleus (MTN), which supplies motor fibres to the masticatory muscles responsible for controlling the closing and opening movement of the jaw, is an oval column of somatotopically organised cells (Palkovits & Brownstein, 1988), and consists of large motor neurons in the human being Mogoseanu et al, 1993;Palkovits & Brownstein, 1988).There have been reports about the human brainstem nuclei studied by morphometric method (Konigmark & Murphy, 1972;Moatamed, 1966;Monagle, 1974;Tomasch & Etemadi, 1962) and a few comparative studies concerning the motor neuron organization of the MTN in rats , as well as a morphometric study of the MTN in developing human brain (Hamano et al, 1988).In this study, we checked whether there were any morphological and morphometrical differences of the MTN among various animals including humans in relation to different jaw sizes. We chose the alligator, the human being and the rat as large, medium and small jaw samples.…”
mentioning
confidence: 99%
“…Assim como vários autores (Travers e Norgren, 1983;Grzanna et al, 1987;Fort et al, 1990;Turman e Chandler,1994;Li et al, 1995;Li et al, 1996;Yasui et al, 1997;Kolta et al, 2000;Luo et al, 2001), observamos que a maior parte das projeções para o Mo5 provém dessa região, porém, observamos alguns núcleos com células retrogradamente marcadas pouco descritos . Os neurônios mesencefálicos recebem densa inervação de fibras imunorreativas a uma série de neurotransmissores e neuromediadores como a dopamina e a noradrenalina além da serotonina ), do fator liberador de corticotrofina (CRF) cujos corpos celulares parecem estar no núcleo central da amígdala (CeA) (Sakanaka et al, 1986), e da orexina (ORX) e óxido nítrico Células retrogradamente marcadas também foram verificadas, com pequena predominância ipsilateral, em núcleos da formação reticular pontina e bulbar, como no núcleo gigantocelular (Gi), núcleo gigantocelular parte alfa (GiA), além da formação reticular pontina parvicelular parte alfa (PCRtA), núcleo reticular intermediário (IRt) e mais caudalmente no núcleo do trato solitário (NTS), o que está de acordo com trabalhos realizados em ratos, gatos e coelhos Mogoseanu et al, 1993;Li et al, 1995;Li et al, 1996;Yasui et al, 1997;Kolta et al, 2000;Luo et al, 2001 Porém, o que pudemos notar foi que a maioria dos autores estava mais preocupada em estudar as marcações retrógradas no tronco encefálico do que possíveis marcações prosencefálicas.…”
Section: Tronco Encefálicounclassified
“…Desta forma, muitos deles nem analisaram cortes prosencefálicos (Mogoseanu et al, 1993;Turman e Chandler, 1994;Li et al, 1995;Li et al, 1996;Yasui et al, 1997;Kolta et al, 2000;Yamamoto et al, 2007 O CRF é um neuromediador relacionado ao eixo hipotálamo-hipófise-supra renal, que participa da liberação de hormônios relacionados ao estresse (Valles et al, 2003). Os neurônios responsáveis por esta ação estão localizados no núcleo paraventricular do hipotálamo mas, no entanto, o CRF é amplamente distribuído no sistema nervoso central sendo encontrado, por exemplo, na amígdala (Potter et al 1994).…”
Section: Tronco Encefálicounclassified